Panggilan Profetik Guru-guru Kristiani dalam Perspektif Pemikiran Paul Tillich - Fransiskus Xaverius Sugiyana; Nerita Setiyaningtiyas; Yustinus J.W. Yuniarto; Ambrosius Heri Krismawanto (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2024)
Abstract. This research explored into the prophetic call of Christian teachers, viewing it through the perspective of theologian, Paul Tillich. Starting from the assumption that that teaching carries profound spiritual significance, the research explores how Tillich's insights impact modern Christian educators in comprehending the prophetic aspect of their vocation. By using a descriptive quantitative approach, this research tried to discover the manifestation of the prophetic dimensions of teachers in their daily lives. Through a survey, researchers explored their perceptions regarding the prophetic calling of teachers. The research result showed that religious teachers demonstrate the meaningfulness of prophetic teacher values through their willingness to be part of an inclusive community, teaching life values using inspirational stories, and practicing Christian values to influence society. The implementation of Paul Tillich's theological insights into the prophetic calling of Christian teachers suggested that Christian pedagogy is a kairos moment when the transformative potential of learners becomes a reality by God's grace.Abstrak. Studi ini mendalami konsep panggilan profetik guru-guru Kristiani melalui lensa teolog terkenal, Paul Tillich. Didasarkan pada keyakinan bahwa panggilan mengajar memiliki signifikansi spiritual yang mendalam, penelitian ini mengeksplorasi implikasi dari wawasan teologis Tillich terhadap pendidik Kristiani kontemporer. Dengan menggunakan pendekatan kuantitatif deskriptif, penelitian ini mencoba untuk menemukan wujud dari dimensi profetik  guru-guru dalam kehidupan sehari-hari mereka. Melalui survey, peneliti menelusuri persepsi mereka mengenai panggilan kenabian para guru. Hasil penelitian menunjukkan bahwa guru-guru agama menampakkan kebermaknaan nilai profetik guru melalui kesediaan untuk menjadi bagian komunitas inklusif, pengajaran nilai-nilai kehidupan dengan menggunakan cerita-cerita inspiratif, dan pengamalan nilai-nilai Kristiani untuk mempengaruhi masyarakat. Implementasi wawasan teologis Paul Tillich ke dalam panggilan profetik guru-guru Kristiani menyatakan bahwa  pedagogi Kristiani adalah momen kairos ketika potensi transformatif peserta didik menjadi kenyataan oleh kasih karunia Allah.